2010
DOI: 10.1364/oe.18.001820
|View full text |Cite
|
Sign up to set email alerts
|

Polarization-multiplexed rate-adaptive non-binary-quasi-cyclic-LDPC-coded multilevel modulation with coherent detection for optical transport networks

Abstract: In order to achieve high-speed transmission over optical transport networks (OTNs) and maximize its throughput, we propose using a rateadaptive polarization-multiplexed coded multilevel modulation with coherent detection based on component non-binary quasi-cyclic (QC) LDPC codes. Compared to prior-art bit-interleaved LDPC-coded modulation (BI-LDPC-CM) scheme, the proposed non-binary LDPC-coded modulation (NB-LDPC-CM) scheme not only reduces latency due to symbol-instead of bit-level processing but also provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 26 publications
0
32
0
Order By: Relevance
“…As aforementioned in section 2, the 4-ary QC-LDPC code used in our experiment was obtained by assigning nonzero elements from GF(4) to the 1s in the parity-check matrix of this binary QC-LDPC code. Further details on nonzero element assignment can be found in [4]. The operational flow can be summarized as follows.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As aforementioned in section 2, the 4-ary QC-LDPC code used in our experiment was obtained by assigning nonzero elements from GF(4) to the 1s in the parity-check matrix of this binary QC-LDPC code. Further details on nonzero element assignment can be found in [4]. The operational flow can be summarized as follows.…”
Section: Resultsmentioning
confidence: 99%
“…Given these definitions, we can describe the layered decoding algorithm by the pseudo code given in Fig.2. The core operation performed at the check nodes of the layered decoder, denoted by Ψ in the pseudo code, is the same as the core operation of the flooding decoder which was described in detail in [4]. The distinguishing feature of the layered decoding algorithm is the utilization of the updated messages faster in decoding.…”
Section: Nonbinary Ldpc Codes and Their Decodingmentioning
confidence: 99%
See 1 more Smart Citation
“…5. We employ regular girth-10 LDPC code with length 16935 and rate 0.8 as the mother code [14]. Sumproduct algorithm is then used in the decoding process.…”
Section: Nonbinary Quasi-cyclic Ldpc Coding For 9-qammentioning
confidence: 99%
“…The FEC operating in large Galois field (GF) that matches the size of multilevel modulation formats, called the non-binary FEC coded modulation, which deals with modulation symbol directly was reported in [3]. Due to the extensively computation complexity of the nonbinary CM, the binary FEC together with a soft de-mapper that maps symbol to bit is widely adopted both in simulation and experimental demonstrations, and it has been shown that capacity approaching performance are possible even with binary CM [4,5].…”
Section: Introductionmentioning
confidence: 99%